When necessity is the mother of disruption: Users versus producers as sources of disruptive innovation - Stephanie Preißner; Christina Raasch; Tim Schweisfurth (Journal of Product Innovation Management, 2023)
This study investigates the sources of disruptive innovation. The disruptive innovation literature suggests that these do not originate from existing customers, in contrast to what is predicted by the user innovation literature. We compile a unique content-analytical dataset based on 60 innovations identified as disruptive by the disruptive innovation literature. Using multinomial and binomial regression, we find that 43% of the sample disruptive innovations were originally developed by users. Disruptive innovations are more likely to originate from users (producers) if the environment has high turbulence in customer preferences (technology). Disruptive innovations that involve high functional (technological) novelty tend to be developed by users (producers). Users are also more likely to be the source of disruptive process innovations and to innovate in environments with weaker appropriability. Our article forges new links between the disruptive and the user innovation literatures, and offers guidance to managers on the likely source of disruptive threats.
Keywords: 650; appropriability regime; disruptive innovation; environmental turbulence; functional novelty; radical innovation; user innovation